Use of TiO2/chitosan nanoparticles for enhancing the preservative effects of carboxymethyl cellulose in paper-art-works against biodeterioration. (July 2018) - Ariafar, Ali Asghar; Afsharpour, Maryam; Samanian, Kouros
Abstract: The main objective of this paper is the optimization and enhancing of the preservation quality of the carboxymethyl cellulose (CMC) polymer against microorganism factors by using titanium dioxide and TiO2 /chitosan nanoparticles. Biological and thermal accelerated aging experiments were carried out on adhesive films and treated paper samples to investigate the influence of TiO2 and TiO2 /chitosan nanoparticles on the properties of the aged adhesive films and treated papers. The antifungal activity of TiO2 and TiO2 /chitosan nanoparticles was investigated against the two fungi species commonly found on library materials: Aspergillus flavus and Aspergillus niger . Our results showed that TiO2 is a desirable material for preserving CMC films and its treated papers, but its problem is that its restricted reactivity in the UV wavelength limits its use in indoor circumstances. TiO2 /chitosan nanoparticles are more effective, even in darkness, and could be successfully applied to optimize the CMC properties. Furthermore, results show that the TiO2 /chitosan nanoparticles decrease the yellowness of CMC adhesive and while not reducing its adherence. Also, this nanoparticle can obviously reduce the oxidation of paper during the aging process, and a slight decrease in the tensile strength and pH of the paper is observed. Graphical abstract: Highlights: A novel antifungal nanocomposites were prepared by the incorporation of TiO2 and chitosan nanoparticles in the CMC adhesive. This investigation attempts to optimize and enhance the preservation quality of CMC against two common fungi: Aspergillus flavus and Aspergillus niger . Our results showed that TiO2 /chitosan nanoparticle is a desirable material for preserving the CMC film and its treated papers even in darkness. Results show that the TiO2 /chitosan nanoparticles prevent the yellowness of CMC adhesive and did not reduce its adherent. TiO2 /chitosan nanoparticle obviously can reduce the oxidation of paper during the ageing process and a slight decrease in tensile strength and pH of paper are observed.